2015
DOI: 10.12688/f1000research.6625.1
|View full text |Cite
|
Sign up to set email alerts
|

Should adults with type 2 diabetes be screened for atherosclerotic cardiovascular disease?

Abstract: Diabetes mellitus is associated with greater risks for cardiovascular diseases (CVD). Multiple noninvasive screening tools for CVD including cardiac CT, carotid intima-media thickness test, myocardial perfusion imaging have been examined in those with diabetes, but the prognostic value of these tests vary and issues remain regarding their cost-benefit ratios, potential harms of radiation, and how they fit into screening algorithms for CVD. We discuss in this report the needs and criteria for screening tests an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Using the Atherosclerosis Risk in Communities Study, a larger US cohort, Nambi et al [43] showed that 23% of patients were reclassified on adding CIMT to traditional risk factors, with a net improvement index of 9.9%. Meta-analysis and pooled cohort studies showed that the addition of common CIMT to traditional risk models was associated with only a modest improvement and may not be clinically useful [44]. CIMT is therefore not recommended in the current AHA/ACC risk assessment guidelines.…”
Section: Carotid Intima-media Thicknessmentioning
confidence: 99%
“…Using the Atherosclerosis Risk in Communities Study, a larger US cohort, Nambi et al [43] showed that 23% of patients were reclassified on adding CIMT to traditional risk factors, with a net improvement index of 9.9%. Meta-analysis and pooled cohort studies showed that the addition of common CIMT to traditional risk models was associated with only a modest improvement and may not be clinically useful [44]. CIMT is therefore not recommended in the current AHA/ACC risk assessment guidelines.…”
Section: Carotid Intima-media Thicknessmentioning
confidence: 99%
“…(Defined ASCVD events do not include peripheral artery disease, heart failure, revascularization, and other atherosclerosis‐related, life‐altering events.) Calcium score can play a particular role for high risk groups having diabetes, rheumatoid arthritis, HIV, etc . Despite great enthusiasm among many physicians for CT coronary calcium score, there is little support for population screening due to its costs (both patient charges and radiation).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium score can play a particular role for high risk groups having diabetes, rheumatoid arthritis, HIV, etc. 10,[14][15][16][17][18][19][20][21][22] Despite great enthusiasm among many physicians for CT coronary calcium score, there is little support for population screening due to its costs (both patient charges and radiation).…”
Section: Introductionmentioning
confidence: 99%